2022
DOI: 10.3389/fphar.2022.915592
|View full text |Cite
|
Sign up to set email alerts
|

Bailing capsule (Cordyceps sinensis) ameliorates renal triglyceride accumulation through the PPARα pathway in diabetic rats

Abstract: Diabetic nephropathy (DN) is a severe diabetic complication of the kidney and is the main cause of end-stage kidney disease worldwide. Cordyceps sinensis (C. sinensis) is not only a traditional Chinese medicine (TCM) but also a healthy food. In China, C. sinensis has been widely used to treat various kidney diseases. Bailing Capsule, which active ingredient is C. sinensis, is approved to treat kidney disease, respiratory disease, and immune disease. However, its underlying mechanism in DN remains unclear. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…SCD is a rate-limiting enzyme that converts saturated fatty acids to monounsaturated fatty acids, leading to the formation of neutral lipid droplets [14]. Thus, SCD plays a key role in fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…SCD is a rate-limiting enzyme that converts saturated fatty acids to monounsaturated fatty acids, leading to the formation of neutral lipid droplets [14]. Thus, SCD plays a key role in fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 38 RCT studies involving 3167 patients with DKD showed that Cordyceps sinensis preparations combined with ACEI/ARB significantly reduced 24-hour urinary protein compared with the ACEI/ARB alone group [standardized mean difference (SMD) = -1.99, 95% confidence interval [CI] (-2.68, P<0.05; -1.31, P<0.01], urinary microalbumin [mean difference (MD) = -37.41, 95% CI (-44.76, -30.06), P<0.01], UAER [MD= -24.11, 95% CI (-30.54, P<0.01), -17.68), P<0.01], and ACR [SMD =1.01, 95% CI (-1.73, -0.29), P<0.01], and no significant difference was found in adverse events between the two groups [118]. Cordyceps sinensis preparation can reduce renal TG accumulation in DN rats by regulating the PPARα pathway, thereby reducing glomerulosclerosis, renal tubulointerstitial injury, and renal fibrosis, as well as glomerular proteinuria and renal tubular proteinuria [119]. Based on the comprehensive metabolomics and pattern recognition technology of ultra-performance liquid chromatography-mass spectrometry, it was found that Cordyceps sinensis preparations may play a role in treating DN by searching abnormal metabolic pathways [120].…”
Section: Other Chinese Patent Medicinementioning
confidence: 95%
“…Using a rat model of unilateral ureteral obstruction (UUO), researchers observed that Cordyceps sinensis can inhibit BAG3 expression, thus reducing renal fibrosis (Liu et al, 2022). The inhibition of the TGF-β1/Smad classic signaling pathway and the reversal of epithelial-mesenchymal transition are among the mechanisms through which Cordyceps sinensis exerts its anti-renal fibrosis effects (Wang et al, 2018;Yang et al, 2020;Zhang et al, 2022). Cordyceps sinensis also exhibits inhibitory effects on the proliferation of human glomerular mesangial cells in vitro (Chen et al, 2019).…”
Section: Go Bioanalysis and Kegg Enrichment Analysismentioning
confidence: 99%